Momentum lost or creating new constellations? Insights from an exercise-at-work project during the COVID-19 pandemic – a mixed methods approach. (March 2023) - Overbye, Marie; Wagner, Ulrik
Exercise-at-work programmes have been identified as venues to decrease inequalities in physical activity and exercise between socioeconomic groups and to improve employees' health and wellbeing. Drawing on a multiple institutional logics perspective and adopting a mixed-methods approach, this paper investigates how employees, exercise-ambassadors and managers at five Danish workplaces experience Covid-19 induced changes to a 1-year exercise-at-work project, and how these changes impacted upon the workplace. Our results suggest that Covid-19 and the altered format of exercise and delivery polarized employees' opportunities for exercise at work. However, the generally positive experiences of exercise-at-work activities and their influence on social environment and collaboration (identified prior to Covid-19 lockdown) remained among those employees who continued with activities. Self-organized adaptions and models of employee exercise which emerged suggest that community logic endured despite the crisis. We show how Covid-19 induced organizational changes led to interplays between institutional logics, with family and state logics becoming more prominent. Specifically, the exercise-at-work programme changed from an aligned model, with complementary logics and minimal conflict, to a model where logics of profession and corporation became dominant at the expense of community logic (exercise-ambassadors activities), but constrained by a state and a family logic.